Effectiveness of project-based learning for enhancing students critical thinking skills: A meta-analysis - Tafakur Tafakur; Heri Retnawati; Ahmad Adnan Mohd Shukri (University of Muhammadiyah Malang, 2023)
Innovative learning models like Project-based learning are believed to encourage not only the achievement of student learning outcomes but also 21st-century skills. Many studies on Project-based learning are related to developing 21st-century skills, one of which is critical thinking, with different results. Therefore, it is necessary to conduct a study that can elaborate on various studies on the effectiveness of Project-based learning on students' thinking skills. This study aims to determine the difference in critical thinking skills between students participating in project-based learning and other models. This study uses a quantitative approach with meta-analysis. The data is secondary data from studies published in journal articles indexed by Scopus and Google Scholar in the last ten years with a total of 29 studies that are suitable for analysis. The estimated aggregate is the difference between groups. Data analysis used Comprehensive Meta-Analysis Vers.3 to calculate and estimate aggregates, draw forest plots, test hypotheses, and analyze biases. The analysis results show that Project-based learning promotes students' critical thinking skills, although moderated by education level and comparative learning strategies. Project-based learning is superior to traditional learning at various levels of education. Project-based learning and other scientific learning are known to support students' critical thinking skills. Teachers can also make PjBL more innovative by utilizing information technology, and the contextual environment, as well as integrating various media, content, and other learning strategies to encourage student critical thinking skills.